Pandangan Dosen Institut PTIQ Jakarta terhadap Perkawinan Poligami: Studi Pasal 56, 57 dan 58 Kompilasi Hukum Islam - Yasin, Zulfatah (Qonuni: Jurnal Hukum dan Pengkajian Islam, 2021)
The movement of gender equality, which is driven by the majority of women activists, rejects all discrimination and injustice received by women, one of the important issues that is often brought to the fore is polygamy. Scholars and scholars also differ on this issue. This study aims to determine the views of the Jakarta PTIQ Institute on polygamy. This research is based on field research that focuses on respondent data and information that has been determined previously with qualitative descriptive analysis methods. The results of this study conclude that polygamous marriage according to the views of PTIQ Jakarta lecturers. Polygamy may be practiced with several conditions, such as being financially capable, being able to do justice between wives, children, and their families. The lecturers of PTIQ Jakarta chose not to practice polygamy due to concerns in the field of livelihood, their fear of not being able to do justice if they have more than one. Besides that, all of them are satisfied and happy with one wife, 2) In a fiqh review, the views of Asatidz Nurul Islam Islamic Boarding School Jember towards polygamy are in line with the views of fiqh scholars. This is reflected in the opinion of those who say that polygamy may be practiced for anyone who meets the qualifications with a limit of four wives.